Edukasi Pencegahan Infeksi Saluran Kemih pada Ibu Hamil Di Kecamatan Jati Agung, Kabupaten Lampung Selatan - Sutarto, Sutarto; Puspita Sari, Ratna Dewi; Utama, Winda Trijayanthi; Mustofa, Syazili (The Journal Publishing, 2025)
This community service program aimed to improve knowledge and preventive behaviors related to urinary tract infection (UTI) among pregnant women in Karang Anyar Village, Jati Agung Subdistrict, South Lampung Regency. The main problems identified in the community included low awareness of safe drinking water, unhealthy urination habits, and limited access to clean water. The activities consisted of health education sessions, interactive discussions, question-and-answer forums, practical simulations, and distribution of educational materials such as booklets and digital media for posyandu (community health post) cadres. Results from the pre–post evaluation showed a significant improvement in participants’ understanding of UTI risks, the importance of boiling water before consumption, and maintaining personal and environmental hygiene. Participants demonstrated a commitment to behavioral change, including avoiding urinary retention and attending regular antenatal check-ups. Posyandu cadres actively participated as facilitators for ongoing community education. This program not only enhanced individual knowledge and awareness but also strengthened the capacity of health cadres and fostered collaboration among academics, health workers, and village authorities. The outputs, including educational booklets, learning modules, and activity documentation, can serve as sustainable resources to support maternal health programs at the community level.